2017
DOI: 10.3390/info8010029
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Modeling of Artificial Bioactive Proteins

Abstract: A total of 32 synthetic proteins designed by Michael Hecht and co-workers was investigated using standard bioinformatics tools for the structure and function modeling. The dataset consisted of 15 artificial α-proteins (Hecht_α) designed to fold into 102-residue four-helix bundles and 17 artificial six-stranded β-sheet proteins (Hecht_β). We compared the experimentally-determined properties of the sequences investigated with the results of computational methods for protein structure and bioactivity prediction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This finding is confirmed by different computational methods. Table 2 shows that the consensus of 10 epitope prediction servers, based on different physicochemical criteria [27,28,29,30,31,32,33,34,35,36,37,38,39,40], also points to the RHSLFHP sequence as the most probable hPSA epitope [23,24,25,26]. The same result is obtained using binding site prediction methods: Phyre2–3DLigandSite and RaptorX (Figure 1) [41,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is confirmed by different computational methods. Table 2 shows that the consensus of 10 epitope prediction servers, based on different physicochemical criteria [27,28,29,30,31,32,33,34,35,36,37,38,39,40], also points to the RHSLFHP sequence as the most probable hPSA epitope [23,24,25,26]. The same result is obtained using binding site prediction methods: Phyre2–3DLigandSite and RaptorX (Figure 1) [41,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Tryptophan fluorescence spectroscopy and microscale thermophoresis are simple, quick, inexpensive and could be used for high-throughput screening [19,20,49,51,52]. The combination of these methods with computational procedures for ligand-acceptor modeling and design enables the quick and simple selection of the antisense peptide structures, which can be used for further development [19,20,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was also shown that modern computational methods enable a new approach to the studies of sense and antisense peptide interactions [20]. Several free web-based services for protein structure prediction and modeling (e.g., I-TASSER, Phyre2, PEP-FOLD 3, CABS-dock) enable accurate proteinpeptide docking, i.e., in silico search for the peptide binding sites [20,28,80,86,87,[89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…An APT-based approach is also useful for peptide interaction and pharmacophore modeling [32,35]. The application of artificial proteins in the context of APT is also a plausible method to derive new antisense modulators of the protein interactions [19,24,88,91,92].…”
Section: Discussionmentioning
confidence: 99%